THE STRATEGY OF MIGUNANI DISABILITY COMMUNITY IN PLANNING INTEGRATED DEVELOPMENT PROGRAM (POSBINDU) FOR DISABILITIES IN SUMBERAGUNG, JETIS, BANTUL - Alfiyanti; Rosita Nasri Yanti (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
This study aimed to analyze the planning strategies of the Integrated Development Post (Posbindu) program in Sumberagung Village. A descriptive qualitative method was employed to gather authentic, natural, and in-depth data through interviews. The results were presented narratively in a creative and detailed manner. The study describes the Posbindu program and analyzes its planning strategies by evaluating strengths and weaknesses, as well as exploring opportunities and threats using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The findings indicate that the Posbindu KDK Migunani program in Sumberagung Village serves as a platform for individuals with disabilities to access health rights within development programs. The research also reveals that the planning strategies for the Posbindu program have been relatively successful, as evidenced by the increasing participation of individuals with disabilities in Posbindu activities